Nanochannel-based sensor for the detection of lead ions in traditional Chinese medicine. Issue 6 (19th January 2021) - Tu, Jiyuan; Zhou, Zhongshi; Liu, Yanju; Li, Tingxian; Lu, Shumin; Xiao, Ling; Xiao, Pingping; Zhang, Guojun; Sun, Zhongyue
Abstract : The nanochannel-based sensor is able to achieve detection of Pb 2+ in TCM samples. Abstract : Lead ions (Pb 2+ ) are used in the quality control of traditional Chinese medicine (TCM) preparations because they are highly toxic to human health. At present, sophisticated analytical instrumentation and complicated procedures for sample analysis are needed for the determination of Pb 2+ . Herein, a simple, fast, and sensitive peptide-modified nanochannel sensor to detect Pb 2+ in TCM is reported, which is based on a Pb 2+ -specific peptide modified porous anodized aluminum membrane (PAAM). This peptide-based nanochannel clearly has the highest selectivity for Pb 2+ when compared to other heavy metal ions, including As 2+, Cd 3+, Co 2+, Cr 2+, Cu 2+, Fe 3+, Hg 2+, Mg 2+, Mn 2+, Ni 2+, and Zn 2+ . Based on linear ranges from 0.01 to 0.16 μM and 10 to 100 μM, the detection limit was calculated to be 0.005 μM. Moreover, this peptide-based nanochannel sensor was successfully used to detect Pb 2+ in complex TCM samples. In addition, when compared with the gold standard atomic absorption spectrophotometry (AAS) method, the recovery of the peptide-modified nanochannel sensor was between 87.7% and 116.8%. The experimental results prove that this new sensor is able to achieve accurate detection of Pb 2+ in TCM samples. Thus, this sensor system could provide a simple assay for sensitive and selective detection of Pb 2+ in TCM, thereby showing great potential in the practical application for the quality control of heavy metals in TCM.